Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1089/ham.2013.1142
|View full text |Cite
|
Sign up to set email alerts
|

Update on High Altitude Cerebral Edema Including Recent Work on the Eye

Abstract: This review summarizes recent research on high altitude cerebral edema (HACE) and on the eye with focus on the retina and optic nerve as visible brain tissue at high altitude. Hemosiderin deposits in the corpus callosum have been characterized as rather specific long-lasting footprints of HACE, indicating a leak of the blood-brain barrier (BBB) and resulting in microhemorrhages. These are compatible with the concept of increased capillary pressure due to venous outflow limitation as suggested by Wilson et al. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 77 publications
0
34
0
Order By: Relevance
“…Most MRI studies in AMS found volume changes of <10 mL between 6 and 16 h of hypoxia with no correlation to AMS symptom scores [43]. These studies could not distinguish between oedema and changes in blood volume, but most of them found decreased water mobility compatible with intracellular swelling associated with AMS.…”
Section: The Brainmentioning
confidence: 97%
“…Most MRI studies in AMS found volume changes of <10 mL between 6 and 16 h of hypoxia with no correlation to AMS symptom scores [43]. These studies could not distinguish between oedema and changes in blood volume, but most of them found decreased water mobility compatible with intracellular swelling associated with AMS.…”
Section: The Brainmentioning
confidence: 97%
“…This is thought to be the producer of tissue edema causing optic disc edema as the swollen of the disc in HACE is not related to elevation of the intracranial pressure (ICP). Hypoxia may be the cause of vessel filtration in the periphery of the retina [11]. Also this may be the causative agent of damage of the wall cells of the vessels leading to the production of hemorrhages [11].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia may be the cause of vessel filtration in the periphery of the retina [11]. Also this may be the causative agent of damage of the wall cells of the vessels leading to the production of hemorrhages [11]. Daniel Barthelmes et al mentioned that higher hematocrit, may contribute to the damage of the endothelial cells [12].…”
Section: Discussionmentioning
confidence: 99%
“…Research into the use of point-ofcare ultrasound scans of the lung and optic nerve sheath diameter is a promising new modality for screening, prediction and early diagnosis of HAPE and HACE respectively, but is still at the experimental stage. [25,26] …”
Section: Clinical Diagnosis: Symptoms and The Lake Louise Symptom Scorementioning
confidence: 99%